LINGUOCULTURAL ANALYSIS OF TRANSLATION OF ART TERMINOLOGY (IN ENGLISH AND UZBEK LANGUAGES) - Sayfiddinova Xurshida (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article is devoted to the research of the problems of art terminology translation as a part of specified language. The problems of term definition are briefly observed. Practical analysis of term synonymy and term polysemy phenomenon was revealed within present work considering to be the most difficult for translation. Moreover, linguocultural aspects of translation of art terminology were discussed.